The electromagnetic compatibility research group: research questions (2010)
This paper summarises the Universidad Nacional de Colombia’s Electrical and Electronic Engineering Department’s Electromag- netic Compatibility Research Group (EMC-UNC) activities during the last 30 years. The group was involved in developing experimental tools during the early 1980s, such as constructing high-voltage apparatus, developing high-voltage practical work for students and observing electrical discharges. These tools enabled the group to spend a decade focused on resolving one of the Colombian electrical sector’s main EMC problems: distribution transformer’s failures caused by lightning. For almost a decade this investigation was focused on understanding the causes of the extremely high failure index in Colombian rural areas, especially in the Rionegro basin. The main result of this investigation was a reduction by one order of magnitude in mean 10% distribution transformer failure rate. During this research work a noticeable pattern was observed of several electrically-isolated me- tallic bodies immersed in an electric field (i.e. floating electrodes). This was led to initiating floating electrode studies and for mulating a new scientific question, “How do corona electrical discharges interact with floating electrodes?” This new research question was dealt with during the second half of the 1990s and the first decade of the 2000s. This investigation was related to using electrostatically-accumulated charge on a floating electrode. This question opened up four research areas: gas discharge physics, generating fast current impulses, harvesting energy from the electric field and the possibility of high impedance current sources. This paper has summarised the most relevant work done by the EMC-UNC group on these topics. This floating electrode research work started by formulating four patents. Fresh research questions for the 2010s were related to measuring lightning electromagnetic pulses (LEMP), intentional electromagnetic interference (IEMI) studies, measuring picoseconds-rise-time impulses, cleaning water by corona discharge and harvesting, accumulating and using small amounts of energy extracted from electric and electromagnetic fields. The future of the EMC-UNC group is closely related to interaction with other groups.